An improved strain path dependent model under multiaxial cyclic loading for simulating material response of low C-Mn steel. (February 2023) - Pandey, Vibhanshu; Arora, Punit; Gupta, Suneel K.; Khutia, Niloy; Dey, Partha Pratim
Graphical abstract: Highlights: A prominent MAKOC model is implemented and validated for triangular waveform. In the limitations of the MAKOC model, an improved MOT model is introduced. The MOT model results in better predictions under out-of-phase triangular waveform. Both models have shown their robustness for circular and rectangular strain paths. Abstract: In this work, a prominent cyclic plasticity model based on modified AbdelKarim-Ohno kinematic hardening rule and Calloch isotropic hardening is implemented and validated w.r.t. test results of low C-Mn steel. In reference to the shortcomings of the model, an improved model based on modified Ohno-Wang and Tanaka non-proportionality parameter is introduced. Since the precise assessment of stress–strain response is an essential precondition for carrying out fatigue life analysis, therefore hysteresis loop responses under various multiaxial LCF loading having different strain paths are compared. The simulation result with the proposed model resulted in improved assessment for non-proportional strain paths.